2008
DOI: 10.1186/1476-069x-7-39
|View full text |Cite
|
Sign up to set email alerts
|

A 10-year time-series analysis of respiratory and cardiovascular morbidity in Nicosia, Cyprus: the effect of short-term changes in air pollution and dust storms

Abstract: Background -: To date, a substantial body of research has shown adverse health effects of short-term changes in levels of air pollution. Such associations have not been investigated in smaller size cities in the Eastern Mediterranean. A particular feature in the region is dust blown from the Sahara a few times a year resulting in extreme PM 10 concentrations. It is not entirely clear whether such natural phenomena pose the same risks.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
163
2
8

Year Published

2012
2012
2023
2023

Publication Types

Select...
3
3
2

Relationship

0
8

Authors

Journals

citations
Cited by 241 publications
(177 citation statements)
references
References 63 publications
4
163
2
8
Order By: Relevance
“…These findings support results obtained for a 10-year time-series analysis of morbidity in Cyprus. Allcause and cardiovascular admissions were 4.8 % and 10.4 % higher on Saharan dust storm days, respectively (Middleton et al 2008). On the Caribbean island of Trinidad, a deterioration in visibility due to increased Saharan dust cover from not dusty (visibility 016 km) to very dusty (visibility07 km) is temporally associated with an increased daily hospital admission rate from 7.8 patients to 9.25 when climate variables such as barometric pressure and humidity were kept constant (Gyan et al 2005).…”
Section: Dust-health Relationship -Publication Datementioning
confidence: 91%
See 2 more Smart Citations
“…These findings support results obtained for a 10-year time-series analysis of morbidity in Cyprus. Allcause and cardiovascular admissions were 4.8 % and 10.4 % higher on Saharan dust storm days, respectively (Middleton et al 2008). On the Caribbean island of Trinidad, a deterioration in visibility due to increased Saharan dust cover from not dusty (visibility 016 km) to very dusty (visibility07 km) is temporally associated with an increased daily hospital admission rate from 7.8 patients to 9.25 when climate variables such as barometric pressure and humidity were kept constant (Gyan et al 2005).…”
Section: Dust-health Relationship -Publication Datementioning
confidence: 91%
“…More recently, it has been shown that the number paediatric hospital admissions increases for up to 7 days from the peak of dust cover (Monteil 2008). Lee et al 2007) and more than one every 2 days according to others Middleton et al 2008;Monteil 2008). A daily PM 10 concentration exceeding 600 μg m −3 recorded during a dust episode in Seoul in 2002 (Hwang et al 2008) 344 μg m −3 were recorded at Nouakchott (Mauritania) in 2000 .…”
Section: Dust-health Relationship -Publication Datementioning
confidence: 99%
See 1 more Smart Citation
“…Daily PM 10 levels over 200 µg/m 3 were suggested for small to medium scale dust events, while a higher cut-off point of 400 µg/m 3 was used to define severe dust events [5,6]. Other studies have used much lower PM 10 levels to identify dust storm days [7][8][9][10].…”
Section: Introductionmentioning
confidence: 99%
“…The impact of air pollution on public health -especially of the airborne particulate matter (PM) -has been of major interest over the last decade to both the air quality management community and regulatory authorities (Heal et al, 2012;Middleton et al, 2008). The European Union Directive on Air Quality 2008/50/EC sets the general legislative framework on the air quality assessment in populated areas (see Supplementary Information, SI, Table S1Table S1)..…”
Section: Introductionmentioning
confidence: 99%